Intention To Buy Products with Environmentally Friendly Packaging in Jakarta, Indonesia - Aloisius Kevin; Feris Julian Budiman; Harsha Prathama Putra; Thea Amelia Suhargo; Tri Dewanti Kusumadewi Prasetyawati (Syntax Corporation Indonesia, 2024)
The objective of this study is to ascertain the elements influencing consumers' inclination to buy goods packaged in environmentally sustainable materials. The factors are consumers’ attitudes towards purchase behaviors, the influence of social factors, effectiveness perception, self-image considerations, community sense, quality of eco-friendly packaging, products with eco-friendly packaging pricing, and environmental knowledge. This research is conducted to complement the discoveries of the preceding research, with the distinction that this study is carried out in Indonesia. Primary data was obtained by conducting a direct survey with a sample size of 393 respondents using convenience sampling methods. This research is measured through scale variables, and is being analyzed with Cronbach Alpha, factor analysis, and other tools to identify the most influential factors to the least one which will be input into the regression model. The findings are that there are seven factors that impacting consumers' intention to purchase in Jakarta, which are the attitude of consumers toward purchasing behaviors, effectiveness perception, the pricing of products with eco-friendly packaging, community sense, self-image considerations, eco-friendly packaging quality, and environmental knowledge.